Performance improvement of Al-alloyed materials via plasma spray coating - SALMAN, SERDAR (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - The aim of the research is to increase piston and engine performance by using ceramic coated pistons instead of pistons which are manufactured from aluminum alloys and having a coated flame chamber. Design/methodology/approach - Thermal torch and thermal shock tests were performed on the pistons and some specimens of 1.5 mm thick were prepared according to ASTM standards; both have the same material characteristics. In the present work, plasma spray technique was used for ceramic coating. Findings - It was found that the ceramic coating, which, when performed properly, has compatible expansion coefficient with the aluminum alloy pistons, increases performance of pistons and engines. Research limitations/implications - Coatings were limited with one type of bonding and two ceramics, and coated parts were subjected to thermal torch and thermal shock tests. Practical implications - For future work, instead of using other coating materials, stable yttria is used as the best coating material with optimum thermal resistance. By this process, working life of the machine parts can be extended and a number of economical advantages may also be obtained. Originality/value - This paper fulfils the identified information and offers practical help to the industrial firms working with ceramic coatings and also to the academicians working on wear of materials.
Keywords: coatings technology; ceramics; spraying; wear resistance; WC-CO COATINGS; WEAR BEHAVIOR; TRIBOLOGICAL PROPERTIES; ZIRCONIA CERAMICS; SLIDING WEAR; GRAIN-SIZE; FRICTION